IMPLEMENTASI MADRASATUL ULA DALAM KELUARGA ISLAM DI ERA DIGITALISASI - Nurliana Nurliana (Kreatifitas Jurnal Ilmiah Pendidikan Islam, 2025)
Madrasatul ula is the first education a child gets, Mistakes in the use of technology can have fatal consequences for a child's growth. Many children are difficult to control in using gadgets due to parents' negligence in guidance and uncontrolled control. The research method uses triangulation through data presentation, data selection and drawing conclusions and analyzed through content analysis. The research findings obtained are that families need to understand their duties as primary educators who are collaborative between fathers and mothers in caring for and guiding children so that children grow in a balanced manner between physical and mental health. The era of digitalization of the role of the family is expected for the development and growth of their children, guiding in all matters that are educational and intelligent children through guided and directed motor and psychomotor sharpening. So that digital media is a positive medium for their child's growth. The need for parental awareness to control the use of technology by children, teach children about the correct use of technology, provide examples of good behavior, with proper implementation, technology can be an effective tool in supporting children's growth and development.